(untitled) - Rider, Elizabeth A (Belmont, CA, 2000)
Includes bibliographical references and indexes; Neal A. Newfield, Ph.D., LICSW (Giver)
Keywords: Feminist psychology; Sex role -- Psychological aspects; Women -- Psychology; Women -- Social conditions -- Psychological aspects; Tâm lý học nữ quyền; Vai trò quan hệ tình dục -- Khía cạnh tâm lý học